ABS 3D printed solutions for cryogenic applications. (March 2017) - Bartolomé, E.; Bozzo, B.; Sevilla, P.; Martínez-Pasarell, O.; Puig, T.; Granados, X.
Highlights: A thermo-mechanical characterization of ABS 3D printed specimens at 77 K is reported, which allows delimiting their use in cryogenic applications. We present three different examples of ABS 3D printed objects providing specific solutions in different cryogenic areas: (i) (SQUID inserts for angular magnetometry, (ii) a support for a metamaterial "magnetic concentrator", and (iii) tools for in vitro techniques. Abstract: 3D printing has become a common, inexpensive and rapid prototyping technique, enabling the ad hoc fabrication of complex shapes. In this paper, we demonstrate that 3D printed objects in ABS can be used at cryogenic temperatures, offering flexible solutions in different fields. Firstly, a thermo-mechanical characterization of ABS 3D printed specimens at 77 K is reported, which allowed us to delimit the type of cryogenic uses where 3D printed pieces may be implemented. Secondly, we present three different examples where ABS 3D printed objects working at low temperatures have provided specific solutions: (i) SQUID inserts for angular magnetometry (low temperature material characterization field); (ii) a cage support for a metamaterial "magnetic concentrator" (superconductivity application), and (iii) dedicated tools for cryopreservation in assisted reproductive techniques (medicine field).